Parameterisation of fission neutron spectra (TRIGA Reactor) for neutron activation without the used of standard - Liew, Hwi Fen (Penerbit UTM, 2008)
Neutron activation analysis (NAA) is a sensitive and reliable technique for both qualitative and quantitative analysis of wide range of elements in various types of samples. The method involves the irradiation of samples and the detection of gamma energies emitted from the isotope s for med from the process of neutron capture. Most NAA were done by comparison method, which is found to have high errors due to the differences in the matrix composition of sample as well a s comparator. The purpose of this study is to demonstrate an alternative technique of activation analysis based on absolute gammarray measurem ents and the direct calculation of elemental concentrations from reaction rates equation of neutron capture process.